A Year Into the Pandemic: The Diversity of Experience Amongst People With Severe Mental Ill Health - Peckham, Emily; Spanakis, Panagiotis; Heron, Paul; Crosland, Suzanne; Johnston, Gordon; Newbronner, Elizabeth; Wadman, Ruth; Walker, Lauren; Gilbody, Simon (Frontiers in Psychiatry, 2022)
Background The COVID-19 pandemic has amplified pre-existing health inequalities and people with severe mental ill health (SMI) are one of the groups at greatest risk. In this study, we explored the effects of the pandemic and pandemic restrictions on people with SMI during the first year of the pandemic. Methods We conducted a longitudinal study in a sample of people with SMI. The inception survey was carried out between July and December 2020. Participants were then re-surveyed between January and March 2021. People were contacted by telephone and invited to take part in the study over the phone, online or by postal questionnaire. Across both waves we asked participants about their physical and mental health, health risk behaviors, well-being, loneliness, and employment status. Results Three hundred and sixty-seven people with SMI completed the inception survey and 249 people completed the follow up. Whilst some people reported no change in their physical (77, 31%) or mental health (60, 24%) over the course of the pandemic 53 (21%) reported a continuing decline in physical health and 52 (21%) reported a continuing decline in mental health. Participants who maintained a daily routine or reported no decline in physical health were found to be associated with no deterioration in mental health (Daily routine OR 2.27, 95% CI 1.11–4.64; no reported physical health decline OR 0.54, 95% CI 0.17–0.70). Participants were less likely to be occupationally active in the first phase of the pandemic compared to before the pandemic and in the second phase of the pandemic. However, there was no one single experience of people with SMI and similar to studies in the general populations a range of different scenarios was experienced. Conclusions We observed a series of factors that might amplify pre-existing health inequalities. Health systems should be mindful of this, and should redouble efforts to set in place changes to practice and policy, which can mitigate these inequalities. Examples might include; raising awareness of the importance of ensuring that people with SMI receive an annual physical health check and supporting people to maintain a daily routine.